One method of formation of the optimal portfolio project of enterprises development - Корхина, Инна Арнольдовна (Eastern-European Journal of Enterprise Technologies, 2012)
The basic stages and positions for the construction optimal model of choice portfolio projects to development of enterprise and variants of the external crediting are described. The chart of construction of model is presented